2021
DOI: 10.1002/fsn3.2113
|View full text |Cite
|
Sign up to set email alerts
|

Maternal protein restriction induces renal AT2R promoter hypomethylation in salt‐sensitive, hypertensive rats

Abstract: Scope We previously demonstrated that protein restriction in utero induced salt‐sensitive hypertension and changed renal levels of angiotensin type 2 receptor (AT2R) in Stroke‐Prone Spontaneously Hypertensive Rat (SHRSP). Here, we investigated if this characteristic alteration of AT2R is related to AT2R DNA methylation profiles. Methods and Results First, we examined the relation between AT2R DNA methylation and its promoter activity in vitro. Luciferase assays revealed a negative correlation between these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Regarding the developmental programming of CKD, altered methylation of angiotensin receptor 1 (AGTR1) has been shown to mediate the effect of prenatal famine exposure on eGFR decline across consecutive generations in humans [110]. In hypertensive rats, it was demonstrated that maternal protein deficiency in addition to a high-salt diet in the offspring resulted in hypertension that was associated with hypermethylation of prostaglandin E receptor 1 (PTGER1) and hypomethylation of angiotensin II receptor type 2 (AGTR2), respectively, in the kidney [111,112]. Further, AGTR1 hypomethylation in the blood was shown to predict CKD progression in HFDfed mice in adulthood [113], supporting an important role for the DNA methylation of angiotensin receptors and the developmental origin of CKD.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Regarding the developmental programming of CKD, altered methylation of angiotensin receptor 1 (AGTR1) has been shown to mediate the effect of prenatal famine exposure on eGFR decline across consecutive generations in humans [110]. In hypertensive rats, it was demonstrated that maternal protein deficiency in addition to a high-salt diet in the offspring resulted in hypertension that was associated with hypermethylation of prostaglandin E receptor 1 (PTGER1) and hypomethylation of angiotensin II receptor type 2 (AGTR2), respectively, in the kidney [111,112]. Further, AGTR1 hypomethylation in the blood was shown to predict CKD progression in HFDfed mice in adulthood [113], supporting an important role for the DNA methylation of angiotensin receptors and the developmental origin of CKD.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Besides the above programming insults, maternal protein restriction has been established as a common developmental origin of hypertension. Studies in rodents have consistently reported that 6-9% protein restriction in pregnant mothers resulted in hypertension in adult offspring (14)(15)(16)(17). Previous studies led to several hypotheses about the underlying mechanisms, involving the suppression of the newborn renin-angiotensin system (18), impairment to nephrogenesis (19), triggering oxidative disruption in the medulla oblongata (20), or hindering the hypothalamic-pituitary-adrenal axis (21).…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II (Ang II) is an important vasoactive substance in human body, which can produce biological effects such as vasoconstriction, pro-inflammation, fibrosis and cell proliferation mediated by angiotensin II type 1 receptor (AT1R), while angiotensin II type 2 receptor (AT2R) may have completely opposite biological effects (Fig. 1 ) [ 6 8 ]. Ang II can be produced a large number in tumor tissues and up-regulate the expression of AT1R, further regulate the activities of signal proteins such as phospholipase-C (PLC), reactive oxygen species, nuclear factor-κappa B and nitric oxide, and affect the growth and metastasis of tumor cells [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%